Impact Of Implementation Of Qanun No. 11/2018 Concerning Sharia Financial Institutions On The System Sharia-Based Profit Sharing With Good Governance As A Moderating Variable - Zulkarnaini, Zulkarnaini; Surbakti, Agustina Br; Kheriah, Kheriah; Inuzula, Lakharis (Universitas Teuku Umar, 2023)
The Aceh Government, specifically the Lhokseumawe City Government, continues to make contributions through various policies, including the enactment of Qanun No. 11 of 2018 regarding Sharia Financial Institutions. This Qanun is applicable to all business entities, including cooperatives, which are currently under close scrutiny by the regional government and supervised by the Cooperatives and Micro, Small, and Medium Enterprises (MSMEs) Service. The growth of Savings and Loans Cooperatives, which plays a significant role in promoting economic development, has been implemented based on the Qanun LKS. However, there are allegations that the existing regulations have not been fully adhered to in accordance with Islamic Sharia principles. Through this research, we aim to assess the impact resulting from the implementation of the Qanun, specifically its influence on the system in use, which is a Sharia-based profit-sharing system. This study seeks to delve deeper into how Savings and Loans Cooperatives, in particular, can thrive and operate more effectively under the established principles of good governance. To achieve this, the research employs Moderated Regression Analysis (MRA) to examine the extent to which good governance plays a role in ensuring that the implementation of Qanun LKS can be effectively carried out through a Sharia-based profit-sharing system. The findings of the research indicate that the implementation of Qanun No. 11 of 2018 concerning LKS significantly affects the Sharia-based profit-sharing system in Savings and Loans-based Cooperatives in Lhokseumawe City. Additionally, it is observed that Good Governance further strengthens the impact of the interactions between the implementation of Qanun No. 11 of 2018 and the Sharia-based Profit Sharing system. This suggests that Savings and Loans-based Cooperatives have started to implement Sharia practices as mandated by the Qanun, although only a limited number of Cooperatives have transitioned to the Sharia system thus far.